PELATIHAN PRODUKSI MEDIA ONLINE UNTUK MENINGKATKAN KAPASITAS SISWA SMK 3 PERGURUAN CIKINI - Alamsyah, Alamsyah; Sukma, Agus Hitopa; Misnan, Misnan; Bachtiar, Alfan; Pranawukir, Iswahyu; Suandi, Fikry (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This Community Service Program aims to improve the skills of SMK 3 Cikini College students in online media production. The implementation method includes technical training ranging from pre-production to post-production of digital content. The results of the activity showed an improvement in students' skills in producing quality online media content, with a sustainability impact in supporting students' abilities in the digital era.